SUBSTANTIVE ASPECT OF THE STRATEGY FOR LINGUISTIC COMPETENCE FORMATION IN ELEMENTARY SCHOOL - Petrovna Ogluzdina, Tatyana; Kirillovna Nikonova, Nina; Sergeevich Khromov, Sergey (Revista Inclusiones, 2019)
This article discusses the components in the basis of the developed linguodidactic model of foreign language competence, which should be formed by elementary school students when learning a foreign language. These components form the substantive basis of the strategy for linguistic competence formation in elementary school. They are highlighted in relation to the following aspects: 1) instrumental and productive (language knowledge, language and speech skills and abilities); 2) cognitive-compensatory (language abilities); 3) reflective (mechanisms of language reflection); 4) affective (attitude to the student’s activities); 5) personal (communicative and personal qualities of the student); 6) activity oriented (educational skills when mastering a language).